Near-surface fragmentation in irradiated copper under two successive shock loading: effects of local temperature re-distribution and helium bubble expansion - Qiang Bao; Haonan Sui; Bao Wu; Xin-Xin Wang; Qi Zhu; Jian-Li Shao; An-Min He; Pei Wang (Materials & Design)
The underlying physical mechanisms of metal materials associated with the effects of helium bubbles on surface damage under complex shock loading remain mysterious, primarily due to the challenges of observing dynamic evolution in situ and in real time. To address this issue, this study conducts molecular dynamics simulations of copper containing helium bubbles. The results clearly demonstrate that these bubbles lead to more devastating surface fragmentation and enhanced micro-jetting in copper under the double shock loading, and two primary mechanisms governing it in metals with defects are proposed to explain it. On the one hand, helium bubbles expanded due to the release of the first shock wave from the right surface, are collapsed under secondary shock wave, resulting in a local temperature increment and re-distribution. Consequently, the near-surface region of copper containing helium bubbles is more susceptible to melting, which diminishes the binding capacity of the copper matrix to the helium bubbles. On the other hand, the helium bubbles serve as energy storage container under shock loading; the energy absorbed from bubble compression during the shock is subsequently released, accelerating the movement of the microjet and causing severe surface damage through helium bubble expansion.